移動援助時におけるベッドの高さの違いが患者におよぼす影響について - 田丸 朋子; 阿曽 洋子; 伊部 亜希; 本多 容子; 木村 静; 鈴木 みゆき; 徳重 あつ子; 細見 明代 (日本看護研究学会雑誌, 2010)
The present study investigates the influence that different bed heights give to patients. 19 healthy women over 70 years old participated in this experiment. One researcher assumed the role of a nurse and transferred subjects in the patient role under two different bed heights: heights adjusted for nurse's work and for patient's sitting on beds. The angle of the neck dorsiflexion and the heart rates were measured. The average of the maximum neck dorsiflexion angle in heights adjusted for patient's sitting on beds was wider than when transfer was done at heights adjusted for nurse's work. The whole time was divided into three areas, and the average and percent changes were calculated. Comparisons of different bed heights revealed no significant differences. The average and percent change of heart rates were analyzed with multiple comparisons. There was no significance in the data of heights adjusted for nurse's work, but there was a significant increase between "before-move" and "during-move" in the data of heights adjusted for patient's standing up from beds. Therefore, the influence on the patient's neck and heart rates can be decreased by adjusting the patient's bed to working height that is easier for nurses. 本研究の目的はベッドの高さの違いが患者に与える影響について検証することである。被験者は70歳以上の健康高齢女性19名とし，患者が昇降しやすい高さと看護師が作業しやすい高さのベッドそれぞれで移動援助を行った。測定指標は頚部後屈角度および心拍数とした。最大頚部後屈角度は看護師の作業しやすい高さに比べ，患者の昇降しやすい高さでの援助時の値が有意に大きかった（ｐ<0.01）。心拍数は平均値および変化率ともに移動前・移動中・移動後のどの区間も有意差はなかった。しかし平均値および変化率の多重比較では，看護師の作業しやすい高さでは差がなく，患者が昇降しやすい高さのベッドでのみ，移動前の値と移動中の値との間に有意な増加が見られた（ｐ<0.01，ｐ<0.05）。以上より，移動援助時にベッドを看護師の作業しやすい高さに調節すると患者の頚部や心拍数への影響が少なくなるといえる。